KIAI AND ISLAMIC BANK (The Typology of Kiai Based on Their Perception and Behaviour toward Islamic Bank) - AM. M. Hafidz MS; Agus Fakhrina (I-Finance Journal, 2019)
This article aims to explain the perceptions and behavior of Moslem scholars (ulama/kiai) on the coast of Central Java toward Islamic banks. It is unassailable that finding out the kiai’s perception and behavior toward Islamic banks becomes unavoidable because the kiai occupies a very important position in the social structure as an agent of social change. In order to have an approriate understanding toward the perception and behavior, this study used qualitative-phenomenological approach. The main source of primary data were obtained from the kiai in Pekalongan region by using purposive sampling technique. Indepth-interview as the prominent method in gaining data was reinforced by observation method. To get validity of data, internal and external validity were performed. The former was taken through four stages, namely triangulation, emic process, member checking and prolonged time; and the latter through transferability. Data were analyzed inductively through three cronological steps, e.i. data reduction, display and conclusion drawing. Based on the perceptions and behavior of scholars toward Islamic banks, this study concludes that there are three categories of kiai. The first is an idealist compromise (kompromis-idealis) which argues that Islamic banks do not fully comply with sharia compliance yet, the use of Islamic banks is compulsory and conventional banks are not substitutes for Islamic banks. The second is a realistic compromise (kompromis realistis) which infers that Islamic banks are not fully accordance with sharia commpliance, the use of Islamic banks is not mandatory, but conventional banks are not substitutes for Islamic banks. The third is resistance (resisten) which argues that Islamic banks are not much different from conventional banks, so making use of Islamic bank is not obligation, and conventional banks substitute Islamic banks.